Effectiveness of the self-fatigue assessment in guiding early postoperative ambulation in gynaecological oncology patients: study protocol for a randomised controlled trial. Issue 6 (1st June 2022) - Du, Qian; Chen, Bo; Xu, Shaoyong; He, Hong; Qin, Xiaomin; Kang, Tongting; Wang, Xu; Huang, Xiaojie
Abstract : Introduction: Enhanced recovery after surgery (ERAS) guidelines strongly recommends that patients be in early postoperative ambulation within 24 hours. This study aims to assess the effectiveness and safety of the self-fatigue assessment method to guide patients' early postoperative ambulation. Methods and analysis: This is a single-centre, randomised, open, parallel-controlled trial. Five hundred and fifty-two patients who meet the inclusion criteria for gynaecological oncology surgery are randomly assigned in a 1:1 ratio to either a self-fatigue assessment group (study group) or a fixed activity distance assessment group (control group). The fixed activity distance group adopts a fixed early postoperative ambulation distance to guide the patient's activity, while the self-fatigue assessment group uses the Borg Exercise Scale to assess the patient's fatigue and stops activity when the fatigue level reaches 5–6. The primary outcome measure is the time to first postoperative flatus. Secondary outcome measures are the time to first bowel movement, the incidence of moderate to severe bloating, the incidence of bowel obstruction or venous thromboembolism, the incidence of adverse events (nausea, vomiting, dizziness), patient satisfaction, sleep quality scores, patient compliance with activities, hospital costs and days in hospital. Ethics and dissemination: This study was approved by the Independent Ethics Committee of Xiangyang Central Hospital affiliated with Hubei University of Arts and Sciences and registered with the China Clinical Trials Registry in May 2021. The results of the trial will be disseminated through open access peer-reviewed journals and abstracts will be submitted to relevant national and international conferences. Trial registration number: CTR2100046035.